Pengembangan Media Pembelajaran Video Animasi Make Up Cikatri Pada Program Double Track di SMA IPIEMS Surabaya - Subiyakto Putri, Ayu Retnoningtyas; Biyan Yesi Wilujeng; Novia Restu Windayani; Nia Kusstianti (Program Studi Pendidikan Tata Rias, 2026)
This research involved the creation of learning resources for the Cikatri make-up topic within the double track program at SMA IPIEMS Surabaya, aiming to foster student creativity. Using a Research and Development (R&D) methodology, the study encompassed six distinct phases. Data was gathered through questionnaires and psychomotor assessments administered to 30 students enrolled in the double track beauty class. Findings indicated that the animated video learning tool achieved a 90% feasibility rating, classifying it as highly suitable. The average cognitive assessment score was 93.28%, with a t-test confirming a statistically significant improvement in learning outcomes. Concurrently, the average psychomotor assessment yielded a score of 93%, meeting the criterion for 100% classical completeness. Student feedback regarding this medium was overwhelmingly positive, registering at 92.67% and falling within the 'very well received' category. In summary, this investigation concludes that the animated video learning media for the Cikatri make-up material is exceptionally suitable for implementation, effectively enhances educational results, and garners a favorable reception from students.